Методи оптимізації тривимірного контенту для ігрового рушія - Рогинський, С. В.; Гаєвий, М. С. (ХНУРЕ, 2023)
In Unreal Engine 5, performance optimization is the process of modifying an engine and a project to make it work more efficiently and execute more rapidly. It generally focuses on improving some aspects of the game’s performance, like frame rate, memory usage, disk space, bandwidth, and many others. Any game creator wants their game to be able to provide the best possible gameplay experience on the widest possible number of chosen devices. The game build should be performed in the most optimal way for a game to provide the acceptable frame rate and experience on a chosen set of devices. Optimization often helps to get to this point.
Keywords: тривимірний контент